2019
DOI: 10.1111/emre.12370
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Disadvantaged: Gender, Spatially Concentrated Deprivation and Nascent Entrepreneurial Activity

Abstract: Drawing on human capital, intersectionality and mixed embeddedness theory, we test hypotheses on the relationship between gender differences in human capital and gender differences in nascent entrepreneurial activity across geographical space, and the moderating effect of spatially concentrated deprivation on this relationship. Using UK data from Global Entrepreneurship Monitor, we find that the disadvantaged position of female nascent entrepreneurs arises from social exclusion, and specifically that the gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 146 publications
(220 reference statements)
1
10
0
Order By: Relevance
“…Intersectionality literature discusses the privileges and disadvantages emanating from the intersection of social positions of gender, race, and ethnicity (Gill and Larson, 2014;Wang and Warn, 2017). A critical element of intersectionality theory is that intersecting social positions have multiplicative rather than additive effects (Dubrow, 2008;Murzacheva, Sahasranamam, and Levie, 2019). Females and people from ethnic minorities are seen to face significant disadvantages in entrepreneurship (Pio and Essers, 2014;Cheng, 2015).…”
Section: Intersectionality Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Intersectionality literature discusses the privileges and disadvantages emanating from the intersection of social positions of gender, race, and ethnicity (Gill and Larson, 2014;Wang and Warn, 2017). A critical element of intersectionality theory is that intersecting social positions have multiplicative rather than additive effects (Dubrow, 2008;Murzacheva, Sahasranamam, and Levie, 2019). Females and people from ethnic minorities are seen to face significant disadvantages in entrepreneurship (Pio and Essers, 2014;Cheng, 2015).…”
Section: Intersectionality Theorymentioning
confidence: 99%
“…Entrepreneurship literature in general utilizes intersectionality theory in studying female entrepreneurs or disadvantaged communities (Carter et al, 2015;Murzacheva et al, 2019). The context of immigrant entrepreneurship additionally opens up the dimension of ethnicity and migrant status as an intersectional influence on entrepreneurship.…”
Section: Intersectionality Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, research based on developed countries often associates women entrepreneurship with the realization of autonomy, equality, selfactualization, and work-nonwork balance (Alkhaled and Berglund, 2018;Braches and Elliott, 2016;Gherardi, 2015). However, studies conducted in less developed countries found that entrepreneurship among women is often considered as a means to survive, be empowered, and move out of poverty (Bruton et al, 2013;Kakabadse et al, 2018;Minniti and Naud e, 2010;Murzacheva et al, 2019;Sutter et al, 2019). Malaysia, being a middle income, developing economy in Southeast Asia, but ranking high for women's active engagement, offers an interesting ground to explore the dynamics of women entrepreneurs' careers.…”
Section: Context Of the Studymentioning
confidence: 99%
“…It indicated that gender influences the way one can access certain resources. Despite the progress research has made, recent studies (Murzacheva, Sahasranamam, & Levie, 2020;Wang, 2019) found discriminatory experiences of women entrepreneurs accompanying the perception that they are somewhat disadvantaged comparatively men entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%